Generating large out-of-plane piezoelectric properties of atomically thin MoS2via defect engineering. Issue 41 (18th October 2021) - Ng, Li-Ren; Chen, Guan-Fu; Lin, Shi-Hsin
Abstract : We calculated the piezoelectric properties of asymmetrically defected MoS2 using density functional theory. Abstract : We calculated the piezoelectric properties of asymmetrically defected MoS2 using density functional theory. By creating uneven numbers of defects on either side of two-dimensional MoS2, the out-of-plane centrosymmetry of the charge distribution is clearly broken, and the out-of-plane piezoelectric response is induced. The largest out-of-plane piezoelectric response is associated with the highest defect ratio for MoS2 to be semiconducting. We calculated the critical defect density of the metal–insulator transition of the asymmetrically defected MoS2 to be 9.90 × 10 14 cm −2 and chemical formula MoS1.22 . The d 33 of the multilayer of optimally defected MoS2 is found to be greater than those of AlN and ZnO, and in the same order of magnitude as lead zirconate titanate. All two-dimensional transition metal dichalcogenides can in principle be fabricated as piezoelectric with this approach. The required defect engineering is readily available with various types of ion irradiation or plasma treatment. By controlling the dose of the ion, the defect ratio and hence the piezoelectricity can be tuned. Such asymmetrically defected transition metal dichalcogenides can easily be integrated into two-dimensional transition metal dichalcogenide based devices, which is hard for conventional piezoelectric thin films to rival.